2018
DOI: 10.15294/dp.v12i2.10826
|View full text |Cite
|
Sign up to set email alerts
|

Vocational High School (SMK) Students Accounting Competence Prediction Model by Using Astin I-E-O Model

Abstract: This research aims to know the descriptive of input, environment, and outcome; analyze the influence of input to outcome; analyze the influence of environment to outcome; analyze the influence of input to environement; and analyze the role of environment in mediating the influence of input to outcome. Student previous achievement consisting of Mathematics and Indonesian National Exam at Junior High School is the educational input. Student engagement consisting of school engagement and class engagement is the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Astin's Input-Environment-Outcomes (IEO) model [18] is adopted frequently to explore the impacts of university study on students. Input is defined as students' characteristics at the time of entry to university, that can be operationalized as demographics, academic backgrounds, and previous learning experiences [19].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Astin's Input-Environment-Outcomes (IEO) model [18] is adopted frequently to explore the impacts of university study on students. Input is defined as students' characteristics at the time of entry to university, that can be operationalized as demographics, academic backgrounds, and previous learning experiences [19].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The authors would like to acknowledge the funding provided by University Grant Committee (UGC) Funding Scheme for Teaching and Learning Related Proposals (2016-19 Triennium) (PolyU6/T&L/ [16][17][18][19].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The model attempts to explain the impact of the environment on student groups and individual development, especially focusing on instructional planning and management policies. However, it does not explain why or how students change in theory but guides researchers to study the impact of higher education experience on students in terms of concepts or methods [10].…”
Section: Theories and Hypothesesmentioning
confidence: 99%
“…Student engagement is part of an educational process which is the easiest one to be controlled by the accounting department. Student engagement has been widely used by previous researchers to measure student participation in academic and non-academic activities at universities (Zakir & Yanto, 2015) and at high school (Harwati & Yanto, 2017). Furthermore, Tam (2002) found that the outcome of education in higher education is highly dependent on the quality of inputs and various experiences while studying at the university.…”
Section: Educational Model In Higher Educationmentioning
confidence: 99%